PENGARUH BIAYA OPERASIONAL TERHADAP LABA BERSIH PADA U.K.M. KERIPIK SEHI SUKABUMI - Aprilyana, Dhany; Wahyu Nugroho, Gatot (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2020)
This study aims to determine how much influence the operational costs have on net income in the “UKM Keripik SEHI” Sukabumi from 2009 to 2013. The variables used in this study are marketing costs, general and administrative costs and net income. The method used in this research is descriptive and associative which aims to obtain descriptive about the characteristics of the variables and to determine the relationship between two or more variables. Basically, want to test the truth of a hypothesis which is carried out through data collection in the field. Based on the results of multiple regression analysis, it can be explained that an increase in operational costs (marketing costs and general and administrative costs) incurred by the company will increase company profits. Or vice versa, a decrease in operating costs (marketing costs and general and administrative costs) incurred by the company will reduce the company's profits. The effect of operational costs on net income in SME Chips SEHI Sukabumi is 41.8%, the remaining 58.2% is influenced by other factors not found in this study.